新加坡华人移民的历史建构 ： 以电视剧《信约》三部曲为例 = The history of Chinese Immigrants in Singapore : a case study of the TV drama the journey - 林美玲 Lin, Meiling (2018)
2015年是新加坡50周年诞辰，新传媒为了庆祝新加坡独立50周年推出了大型历史剧《信约》三部曲。第一部曲《信约：唐山到南洋》在2013年推出、随后在2014年和2015年陆续推出第二部曲《信约：动荡的年代》与第三部曲《信约：我们的家园》。本文以《信约》三部曲为例，研究新加坡电视剧对新加坡华人移民史的建构。电视剧从第一代华人移民的故事说起，在19世纪初中国人从“唐山”来到“南洋”，他们主要是来自广东和福建地区的农民。当时正中国面临着内忧外患，战争和天灾不断，而新加坡刚刚开埠，英国殖民者招募大量的劳工。为了生活，新客来到南洋工作挣钱，希望在存够钱后衣锦还乡。一开始他们对这片土地没有任何感情，但随着时间的推移，他们对新加坡的情感逐渐发生变化。第二代土生土长的华人开始参与本地政治，他们的情感开始转向新加坡。新加坡华人移民对这片土地的情感也从落叶归根转变为落地生根。1965年新加坡独立，举国上下齐心合力发展国家建设。为了加强新加坡人的身份认同，新加坡政府采用多种渠道提高国家意识，广播局是其中一项重要的宣传渠道。因此，《信约》三部曲与政府立场一致，阐述新加坡华人移民的历史建构，以及其背后的国家意识。 As Singapore celebrates 50th anniversary of independence in 2015,Singapore's Mandarin television channel MediaCorp Channel 8 launched a historical trilogy series titled "The Journey". It is a transmedia project about the story of Singapore which aired from 2013 to 2015. It consists of three segments: A Voyage, which details early settlers who arrived in Singapore, Tumultuous Times, which is about the Second World War and Singapore's subsequent journey towards independence and Our Homeland, which tells of Singapore's progress as a nation. This thesis uses the trilogy series as an example to study portrayals of Singaporean Chinese immigrant history in local dramas. The trilogy series begins in the early 19th century when the first generation of Chinese immigrants arrived in "Nanyang" from “Tangshan”. In a period where China was facing internal and external conflicts such as wars and natural disasters, these immigrants were mainly farmers from the provinces of Guangdong and Fujian. Singapore had just been occupied by British colonialists and a large scale effort to recruit labor workers begun. With these job opportunities at sight, Chinese immigrants started to migrate to Singapore. They had hopes of improving the standard of living of their families back home and to earn enough savings to eventually return to their hometowns. In the beginning, they did not feel a strong sense of belonging to Singapore yet as time went on, their perspectives of Singapore gradually changed. After the Second World War, the second generation of migrants began to participate in local politics and their sense of belonging started to build up. Overtime, these Chinese immigrants started to feel a sense of belonging to Singapore. Eventually in 1965, the year Singapore gained independence, the entire nation made concerted efforts to develop a national identity. In order to strengthen the identities of new generation, the Singapore government adopted a variety of measures to raise national awareness. News media became one of the most important channels of publicity. As such, the trilogy series "The Journey" is in line with the government's position, expounding on the historical portrayal of early Singaporean Chinese immigrants and national awareness.